Dampak Faktor-Faktor Penentu Purchase Intention Liquid Vape Tetra di Instagram dengan Attitude Toward the Influencer Sebagai Intervening Variable - Adinda Julian S; Marcellia Susan (Jurnal Informatika Ekonomi Bisnis, 2023)
The purpose of this study was to determine the impact of the determinants of Tetra liquid vape purchase intention on Instagram with attitude toward the influencer as an intervening variable. An influencer who has an Instagram account named jee_vanka (Jessica Rima Rahmayanti) is the subject of this study. This research was conducted quantitatively with quantitative descriptive analysis techniques, and 100 respondents were taken for the research sample. Data is processed using SmartPLS software. The results of the analysis and testing of the hypothesis show that the factors have a significant effect on the attitude toward the influencer and have a significant impact on the purchase intention of liquid vape Tetra on Instagram.